REBRANDING BURGERMAN SEBAGAI UPAYA MEMPERLUAS SEGMENTASI PELANGGAN - Adam, Dhafi Kusuma; Dewanto, Thomas Hanandry; Bahruddin, Muh (Jurnal ArtNouveau, 2013)
The Cafe is a place to relax or gather with friends. Look at the growth of the economy of the city of Surabaya since last five years increased, various efforts undertaken in order to reach the largest market share. One of the efforts that the company can do is to form a brand identity that is capable of providing imagery for buyers who then stick in the minds of consumers. The purpose of this design is to know how to design your brand in an effort to expand the Burgerman segmenting customers ranging in age from 18 to 40 years old. The design is done with the approach of the survey, interviews and existing studies in order to formulate the concept of design. Data were analyzed using the indicator: STP, advantages, limitations, opportunities, challenges as well as USP (Unique Selling Proposition). From the results of the analysis and the design of the paper found that the desire to aim burgerman target market and uniqueness by Burgerman has not looked at the brand